Research on New Approach to Patient Specific Instruments for Improving Mechanical and Anatomical Alignment Accuracy during Total Knee Arthroplasty - Reisinafchi, Behnam (Universiti Teknologi PETRONAS, 2017)
Most people who undergo knee replacement surgery are between the ages from 50 to 70 and sixty percent of the knee replacement recipient are women. The Total Knee Arthroplasty (TKA) is a popular method to replace the actual knee with a mechanical part. Thistechnique called Patient Specific Instruments (PSI) which also brings several important and sensitive advantages such as decreasing operative steps and time, loss of blood and pain. However, the existing design of the jigs has not improved the accuracy significantly and led to many post-surgical issues for patient as the bone cutting is not accurate. It is challenging for surgeons to have accurate knee alignment and obtain the perfect cuts during TKA as it requires time and high skills. The conventional jigs and the modern jigs have their pros and cons and they are yet to be tested from the aspects of accuracy, limb alignment and pressure distribution.